Analysis of students' mental health through the perspective of tarbawi hadiths using systematic literature review (SLR) - Alfiah Alfiah; Arbi Arbi; Arwan Arwan; Suhaimi Suhaimi; Miftahuddi Miftahuddi; Abu Anwar; Andi Murniati; Istiqomah Istiqomah; Darmawati Darmawati; M. Fahli Zatrahadi; Nilma Zola (Konselor, 2021)
The mental health of students in the perspective of the hadith tarbawi is not explained directly. However, these hadiths provide insights indirectly in the study of mental health. The purpose of this study was to find out the mental health of students in the perspective of tarbawi traditions. This study uses the Systematic Literature Review (SLR) qualitative research method as a form of process of identifying, evaluating, and interpreting all available study materials in an effort to provide answers to certain research questions. Documents found in the period from 1768 to 2021 reach 200 publications. Then a limitation was carried out which fulfilled six Quality Assessments so that only 6 articles were selected. Then the six articles were coded with the help of Nvivo software. The results showed that students' mental health in the perspective of hadith tarbawi found three things, namely the development of resilience in students, social encouragement and also maintaining positive relationships with the surrounding environment. This is what is able to instill a good attitude in students and give birth to a healthy soul.